Art Editions 1 : Editionen heutiger Kunst: Druckgraphik, Objekte, Wandarbeiten. - Schellmann, Köln; Schellmann, München; Schellmann, New York (Köln : Edition Schellmann, 1995)
Arakawa ; Artschwager ; Arman ; Armleder ; Baldessari ; Baselitz ; Baumgarten ; Becher ; Beuys ; Bickerton ; Brown ; Botanski ; Buren ; Chamberlain ; Chia ; Christo ; Clegg & Guttmann ; Clemente ; Cragg ; Cucchi ; Darboven ; De Maria ; Fischl ; Flavin ; Fleury ; Förg ; Gilbert & George ; Gonzalez-Torres ; Gober ; Graham ; Grünfeld ; Halley ; Hamilton ; Haring ; Heizer ; Hirst ; Hockney ; Holzer ; Horn ; Hütte ; Immendorf ; Johns ; Jones ; Judd ; Kabakov ; Kelley ; Kelly ; Kienholz ; Kirkeby ; Knoebel ; Komar and Melamid ; Koons ; Kounellis ; Kosuth ; Lafontaine ; Lawler/McCollum ; LeWitt ; Lichtenstein ; Long ; Longo ; Lüpertz ; Mangold ; Mapplethorpe ; Marden ; McCollum ; Merz, Gerhard ; Merz, Mario ; Mucha ; Mullican ; Nauman ; Oldenburg ; Paik ; Paladino ; Palermo ; Paolini ; Penck ; Polke ; Prince ; Rainer ; Rauschenberg ; Reinhardt ; Richter ; Rollins & KOS ; Rosen ; Rosenquist ; Rückriem ; Ruff ; Ruthenbeck ; Salle ; Schnabel ; Serra ; Sherman ; Sieverding ; Simpson ; Steinbach ; Stella ; Tapies ; Tuttle ; Twombly ; Ungers ; Vaisman ; Walther ; Warhol ; Weiner ; West ; Whiteread ; Winters ; Wool ; Zobernig
Duits & Engels
boek